A Frequency-Domain Imaging Algorithm for Highly Squinted SAR Mounted on Maneuvering Platforms With Nonlinear Trajectory - Li, Zhenyu; Xing, Mengdao; Liang, Yi; Gao, Yuexin; Chen, Jianlai; Huai, Yuanyuan; Zeng, Letian; Sun, Guang-Cai; Bao, Zheng (IEEE transactions on geoscience and remote sensing, 2016)
The imagery of highly squinted synthetic aperture radar mounted on maneuvering platforms with nonlinear trajectory is a challenging task due to the existence of acceleration and the cross-range-dependent range migration and Doppler parameters. In order to accommodate these issues, a frequency-domain imaging algorithm based on tandem two-step nonlinear chirp scaling (TNCS) with small aperture is proposed. For the cross-range-dependent range cell migration (RCM) caused by the linear range walk correction and acceleration, the first-step NCS is introduced to suppress this dependence and realize the unified RCM correction. Based on the differences between full-aperture and small-aperture data in the cross-range processing, the second-step NCS is introduced in frequency domain to equalize the cross-range-dependent Doppler parameters, for cross-range processing is more sensitive to the cross-range dependence than range processing. Furthermore, a novel geometric correction method based on inverse projection is utilized to eliminate the negative effects caused by the imaging processing. Simulation results and real data processing are presented to validate the proposed approach.